Peer Counselling: An Outreach Program in a Home for the Aged - France, M. Honoré; Gallagher, Elaine M. (Canadian Journal of Counselling and Psychotherapy, 2011)
This paper is an evaluation of the effectiveness of a peer counselling training program in a home for the aged in Victoria, B.C. The goal of the program was to expand the number of helpers available and involve more residents in their self-care. The results indicate that the training model used is an effective method of teaching helping skills to residents of a nursing home.